Population-based survey of prevalence, causes, and risk factors for blindness and visual impairment in an aging Chinese metropolitan population - Hu, Jian-Yan; Yan, Liang; Chen, Yong-Dong; Du, Xin-Hua; Li, Ting-Ting; Liu, De-An; Xu, Dong-Hong; Huang, Yi-Min; Wu, Qiang (International journal of ophthalmology, 2017)
AIM： To assess the prevalence, causes, and risk factors for blindness and visual impairment among elderly （〉60 years of age） Chinese people in a metropolitan area of Shanghai, China. METHODS： Random cluster sampling was conducted to identify participants among residents ≥60 years of age living in the Xietu Block, Xuhui District, Shanghai, China. Presenting visual acuity （PVA） and best-corrected visual acuity （BCVA） were checked by the Early Treatment Diabetic Retinopathy Study （ETDRS） visual chart. All eligible participants underwent a comprehensive eye examination. Blindness and visual impairment were defined according to World Health Organization （WHO） criteria. RESULTS： A total of 4190 persons （1688 men and 2502 women） participated in the study, and the response rate was 91.1%. Based on PVA, the prevalence of blindness was 1.1% and that of visual impairment was 7.6%. Based on BCVA, the prevalence of blindness and visual impairment decreased to 0.9% and 3.9%, respectively. Older （〉80 years of age） women, with low educational levels and smoking habits, exhibited a significantly greater chance for blindness and visual impairment than did those with high educational levels and no smoking habits （P〈0.05）. Based on PVA and BCVA, the main causes of blindness were cataract, myopic maculopathy, and age-related macular degeneration （AMD）. CONCLUSION： Our findings help to identify the population in need of intervention, to highlight the need for additional eye healthcare services in urban China.